Discerning host plant resistance sources in common bean (Phaseolus vulgaris) against root-knot nematode (Meloidogyne javanica) infection - M, Devindrappa; Singh, Bansa; T, Basavaraja (The Indian Journal of Agricultural Sciences, 2023)
From this study we could conclude that, resistant cultivars are the single effective solution to the management of root-knot nematode population to avoid crop losses. Also, it is essential to use resistant cultivars in situations where nematodes are present and when control is advantageous to yields. However, the reported moderately resistant cultivars, viz. Gujarat Rajmash, Amber (IPR 96-4) and HUR15 belong to secondary gene pool with cross-compatibility to cultivated common bean. Therefore, it may be further used in the pre- breeding programme for developing resistant common bean cultivars against root knot nematodes.